2014
DOI: 10.1007/s12602-014-9155-5
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Probiotic Lactobacillus Strains from Traditional Kurdish Cheese

Abstract: In this study, the probiotic potential of Lactobacillus strains isolated from traditional Kurdish cheese was investigated. The Lactobacillus strains were examined for resistance to gastric acidity and bile toxicity, antimicrobial activities, autoaggregation, coaggregation, hydrophobicity, adhesion to Caco-2 cells, and antibiotic susceptibility. The results showed that all strains tested tolerate acid gastric conditions (pH 2.0 and 3.0), and all of them were bile resistant (at 0.3 and 1% concentration). Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 27 publications
7
43
1
2
Order By: Relevance
“…Some isolates of chicken origin exhibited even 100% survival rate at pH of 2.0, while others showed no viability at those conditions (Garriaga et al 1998, Lee et al 2008, Bujnakova et al 2014. Hashemi et al (2014) described significantly lower viability of lactobacilli after 2 h of incubation at the pH 2 or in 0.3% of bile salt, but all evaluated bacteria were obtained from traditional kurdish cheese. It is well documented that lactobacilli isolated from GIT are able to tolerate low pH and bile salt, as compared to strains obtained from fermented food products (Ehrmann et al 2002, Koll et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Some isolates of chicken origin exhibited even 100% survival rate at pH of 2.0, while others showed no viability at those conditions (Garriaga et al 1998, Lee et al 2008, Bujnakova et al 2014. Hashemi et al (2014) described significantly lower viability of lactobacilli after 2 h of incubation at the pH 2 or in 0.3% of bile salt, but all evaluated bacteria were obtained from traditional kurdish cheese. It is well documented that lactobacilli isolated from GIT are able to tolerate low pH and bile salt, as compared to strains obtained from fermented food products (Ehrmann et al 2002, Koll et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Table 14.1 shows a list of Lactobacillus strains isolated from traditional Iranian cheeses that are usually considered as probiotics. Tolerance to acid and bile, ability to adhere to the gastrointestinal mucosa, competitive exclusion of pathogens, and desirable antibiotic susceptibility patterns Tajabadi Ebrahimi et al, 2011;Hassanzadazar et al, 2012;Hashemi et al, 2014a) are some of the common criteria that have been used for the selection of these microorganisms as probiotic. Probiotic characteristics of these bacteria will be discussed below on the basis of the existing literature.…”
Section: Isolation and Identification Of Candidate Probiotic Strains mentioning
confidence: 99%
“…On the other hand, ingestion of probiotic strains with food or dairy products raises the pH in the stomach to 3.0 or higher (Iñiguez-Palomares et al, 2007). All these studies reported a growth delay of Lactobacillus strains in the presence of bile salts that were strain specific (Hassanzadazar et al, 2012;Hashemi et al, 2014a;Tofangsazan, 2014). Bile is an aqueous solution made up of bile acids, cholesterol, phospholipids, and the biliverdin, which gives the bile its yellow-green color.…”
Section: Isolation and Identification Of Candidate Probiotic Strains mentioning
confidence: 99%
See 2 more Smart Citations